Improving the efficiency of using capital at BaoViet group - Phan, Dinh Tam (2020)
Bao Viet Group is constantly developing, confirming its leading position in the field of insurance finance in Vietnam. The Group is gradually promoting internal resources to attract outside resources to develop equity from production and business efficiency. The Group's member companies have had a relatively stable growth, making an important contribution to the Group's business performance. However, data analysis and reality show that capital structure is still more unreasonable, less investment portfolio, current investment is not effective, effective use of assets is not really high, mechanism. The policy is still inadequate, the efficiency index is not low, but the potential for risk reduction in the following years. These shortcomings are due to many different reasons, but the research results have shown that one of the main causes affecting the financial and insurance market situation in Vietnam is becoming increasingly fierce. Therefore, in order to improve the efficiency of capital use, the Group's parent company needs to focus on solutions to promote investment, diversify investment fields, actively use cross-selling and promote products trademark, maintains the leading position in Vietnam's financial and insurance industry